Brain Activation during Perception and Anticipation of Dyspnea in Chronic Obstructive Pulmonary Disease - Esser, Roland W.; Stoeckel, Maria C.; Kirsten, Anne; Watz, Henrik; Taube, Karin; Lehmann, Kirsten; Magnussen, Helgo; Büchel, Christian; von Leupoldt, Andreas (Frontiers in Physiology, 2017)
Background: Dyspnea is the impairing cardinal symptom in COPD, but the underlying brain mechanisms and their relationships to clinical patient characteristics are widely unknown. This study compared neural responses to the perception and anticipation of dyspnea between patients with stable moderate-to-severe COPD and healthy controls. Moreover, associations between COPD-specific brain activation and clinical patient characteristics were examined. Methods: During functional magnetic resonance imaging, dyspnea was induced in patients with stable moderate-to-severe COPD (n = 17) and healthy control subjects (n = 21) by resistive-loaded breathing. Blocks of severe and mild dyspnea were alternating, with each block being preceded by visually cued anticipation phases. Results: During the perception of increased dyspnea, both patients and controls showed comparable brain activation in common dyspnea-relevant sensorimotor and cortico-limbic brain regions. During the anticipation of increased dyspnea, patients showed higher activation in hippocampus and amygdala than controls which was significantly correlated with reduced exercise capacity, reduced health-related quality of life, and higher levels of dyspnea and anxiety. Conclusions: This study suggests that patients with stable moderate-to-severe COPD show higher activation in emotion-related brain areas than healthy controls during the anticipation, but not during the actual perception of experimentally induced dyspnea. These brain activations were related to important clinical characteristics and might contribute to an unfavourable course of the disease via maladaptive psychological and behavioural mechanisms.